Aplicación de mucílago de cacao como fuente de azúcares en el proceso fermentativo del scoby (Symbiotic Culture Of Bacteria and Yeast) para obtener una bebida fermentada - Morales Moreira, Ariel Fernando (2022)
Cocoa mucilage is an extraordinary source for fermentation processes, since its composition contains mostly sugars, yeasts and minerals. In the present project, it was used as a base for the elaboration of a fermented beverage in substitution of normal sugar, thus demonstrating an optional use for this type of product that is sometimes considered as a simple waste of cocoa, thus giving it an added value and enhancing its use. The main objective of the research was to evaluate the application of cocoa mucilage in concentrations of 15, 20 and 30%, as a source of sugars in the fermentation process of scoby (Symbiotic Culture Of Bacteria and Yeast) to obtain a fermented beverage based on black and green tea. An AxB statistical design was applied to compare the means of the treatments, INFOSTAT statistical programs were used to perform the analysis of variance, and STATGRAPHICS was used to compare the differences of the means by means of the TUKEY significance test. Physical and chemical analyses were carried out on the fermented beverage, as well as microbiological analyses to detect the presence of microorganisms. The results of these analyses were positive, as no microorganisms were detected, which indicates that the product complies with the established standards, of the treatments studied, the one that presented the best characteristics both in the analyses and in terms of acceptability measured by tasting was a1 b1 = (20% concentration) and (black tea). Key words: Mucilage, Fermentation, Microorganisms, Scoby, Kombucha.